5-Aminosalicylic Acid Enemas in the Maintenance of Remission in Distal Ulcerative Colitis and Proctitis. (1987) - Sutherland, Lloyd R; Martin, Francois
Abstract : A randomized clinical trial of the efficacy and safety of two different dosages of 5-aminosalicylic acid (5-ASA) enemas was carried out in 29 patients who had documented ulcerative colitis involving up to 50cm of distal colon. All patients were in remission or had minimal disease activity (Disease Activity Index [DAI] less than 4) at the time of study entry. The two patient groups were similar in terms of age, sex ratio and disease activity. Further significant reduction in DAI occurred during the first three months of the study. Five patients (two in the 2 g group and three in the 4g group) relapsed over the next six months. There were no significant differences in DAI of the two groups over the six month study period (ANOVA for repeated measures). Six patients dropped out of the study all of whom were in remission when last seen (mean follow-up 3. 3 months). In this preliminary study, 2 g enemas were shown to be as effective as 4 g enemas in maintaining remission in patients with ulcerative colitis confined to the distal colon.